Centrosomal protein TAX1BP2 inhibits centrosome-microtubules aberrations induced by hepatitis B virus X oncoprotein. (1st November 2020) - Li, Sai-Kam; Tang, Hoi-Ching; Man-Hon Leung, Manton; Zou, Wenjun; Chan, Wing-Lim; Zhou, Yuan; Oi-Lin Ng, Irene; Ching, Yick Pang
Abstract: Liver cancer (hepatocellular carcinoma, HCC) is one of the most prevalent cancers worldwide. Several etiological factors of HCC, including hepatitis B or hepatitis C virus infection, liver cirrhosis and aflatoxin B1 intake has been identified. HBx, which is an oncogenic protein encoded by the hepatitis B virus, is strongly associated with hepatocarcinogenesis. Using stable HBx-expressing cell, we showed that HBx induced chromosome gain, with amplification of centrosomes numbers and deregulation of centrosome ultrastructure. To dissect the mechanism for chromosome instability, our result revealed that HBx contributed to a hyperactive centrosome-microtubule dynamics by accelerating microtubule nucleation and polymerization. Further investigations suggested that HBx interacted with a centrosome linker protein TAX1BP2, which has previously been shown to function as an intrinsic block of centrosome amplification and a tumour suppressor in HCC. Restoring TAX1BP2 was able to block HBx-mediated centrosome amplification and abolish the HBx-mediated centrosome aberration, thereby suppressing chromosome instability. Thus, we demonstrate here a mechanism by which HBx deregulates centrosome-microtubule dynamics through interacting with TAX1BP2, which underlines the possibility of restoration of TAX1BP2 to rescue cells from chromosome instability. Highlights: HBx promotes chromosome instability through centrosome-microtubule hyperactivity. HBx localizes at the proximal end of centrioles. HBx interacts with C-terminus of a centrosome protein and tumour suppressor TAX1BP2. Expression of TAX1BP2 represses the effect of HBx on chromosome instability.